(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the crucial role of spoken interaction in the language learning process, demonstrating its impact on the development of all four language skills: reading, writing, listening, and speaking.This research aims to describe the types of classroom interaction and the roles of classroom interaction in speaking classes.Interaction that occurs in the classroom can help students improve their speaking skills..